2017
DOI: 10.5539/jas.v9n9p210
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing Yields, Nutrient Uptake and Balance for Mustard-Mungbean-T. Aman Rice Cropping Systems through Nutrient Management Practices in Calcareous Soils

Abstract: The experiment was conducted to measure crop yields, nutrient concentration, nutrient uptake and balance by using different nutrient management practices for mustard-mungbean-T. aman rice cropping system in calcareous soil of Madaripur, Bangladesh. Different nutrient management practices were absolute nutrient control (T 1 ); farmer's practice (T 2 ); AEZ based nutrient application (T 3 ) and soil test based nutrient application (T 4 ). The practices were compared in a randomized completely block design with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Quddus et al 135 Protein contein in fieldpea seed was estimated by multiplying the % N content of seed with pulses food factor 5.30 (FAO, 2018). Crop uptake of Zn and B was estimated by multiplying the total dry matter yields of fieldpea with corresponding Zn and B concentrations (Quddus et al, 2017).…”
Section: Soil and Plant Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Quddus et al 135 Protein contein in fieldpea seed was estimated by multiplying the % N content of seed with pulses food factor 5.30 (FAO, 2018). Crop uptake of Zn and B was estimated by multiplying the total dry matter yields of fieldpea with corresponding Zn and B concentrations (Quddus et al, 2017).…”
Section: Soil and Plant Analysismentioning
confidence: 99%
“…The yield of pulses in Bangladesh is low due to many reasons: nutrient deficiency (including micronutrient) is one of them (Quddus et al, 2014). Nutrient deficiency in soil leads to reduction of pulses productivity .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Valenciano et al [16] found that Zn application was more efficient in chickpea when it was applied in conjunction with boron and molybdenum. Quddus et al [17] reported that many soils of Bangladesh are deficient in zinc (Zn), boron (B), and molybdenum (Mo), which causes poor crop yields. The beneficial effects of these three micronutrients on groundnut, soybean, chickpea, and mungbean have already been reported in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…Although, rotations has notable effects on soil nutrients content, essentially related to nitrogenfixating (Carpenter-Boggs et al, 2000), several researchers have concluded that there are others effects outside that, which can be clarified by soil mineral contents (Wright, 1990;Bullock, 1992 and; improved soil structure (raimbault & Vyn, 1991); improve nutrient use efficiency (Karlen et al, 1994 andTanaka et al, 2005); increased soil organic matter contents,as a result of large amount of crop residue was left in the soil after harvest (Campbell & Zentner, 1993;Bremer et al, 2008;Adiku et al, 2009;Ali et al, 2010;Zhang et al, 2012 andSexton et al, 2014); also crop rotation can have substantial positive influence on plant nutrients uptake and mitigating the effects of limited nutrient availability of N, p, K and Ca for cereal crops (Bolton et al, 1976;Higgs et al, 1976;Welch, 1976;riedell et al, 1998;Brozyna et al, 2013 andAbdul Quddus et al, 2017). Marginal benefit also can be gained in managing the production of crop residues by adopting crop rotation system as compared with monoculture, when high biomass and crop residue were formed (such as corn) are recommended to sequence with crops that produce more subtle residue similar soybean.…”
Section: Rotations and Soil Nutrient Statusand Availabilitymentioning
confidence: 99%